Knowledge construction in blended learning and its impact on students' academic motivation and learning outcomes - Younas, Muhammad; El-Dakhs, Dina Abdel Salam; Jiang, Yicun (Frontiers in Education, 2025)
BackgroundBlended learning combines the strengths of online and face-to-face education to cater to students' varying needs and preferences. However, in blended learning environments, learners often encounter challenges stemming from the lack of support and guidance compared to traditional face-to-face teaching methods. Computer-Integrated Learning Assistance (CILA), which utilizes AI technologies, provides real-time support and guidance to learners in this context.ObjectiveThe current study analyzed the role of technological knowledge construction in blended learning and how it impacts students' academic motivation and learning outcomes.MethodThe study is qualitative in nature and participants were recruited using a purposive sampling technique. Ten university professors were selected for the study. Qualitative data collection was performed using a semi-structured interview guide. The collected data were analyzed utilizing the NVivo 13 software.ResultThe study findings suggest that blended learning is a flexible way of learning which saves money and time as students can easily access their course materials. Additionally, blended learning increases students' learning motivation, facilitates both place and peace of learning, and has the potential to enhance student learning outcomes to improve their thinking ability.ConclusionThe use of blended learning helps with evaluation and continuous improvement. Based on the study findings, it is concluded that teachers can guide learners through direct interaction in classes and reinforce their understanding of the subject matter through the interaction, accessibility, and flexibility of multi-media and online-created environments in blended courses.